Effects of Tenapanor on Cytochrome P450‐Mediated Drug‐Drug Interactions. Issue 5 (16th March 2017) - Johansson, Susanne; Rosenbaum, David P.; Ahlqvist, Marie; Rollison, Helen; Knutsson, Mikael; Stefansson, Bergur; Elebring, Marie
Abstract: Tenapanor (RDX5791, AZD1722) is an inhibitor of sodium/hydrogen exchanger isoform 3 in development for the treatment of constipation‐predominant irritable bowel syndrome and the treatment of hyperphosphatemia in patients with chronic kidney disease on dialysis. We aimed to investigate whether tenapanor inhibits or induces cytochrome P450s (CYPs). In vitro experiments assessing the potential of tenapanor to affect various CYPs indicated that it could inhibit CYP3A4/5 (IC50 0.4‐0.7 μM). An open‐label, phase 1 clinical study (NCT02140268) evaluated the pharmacokinetics of the CYP3A4 substrate midazolam when administered with and without tenapanor. Healthy volunteers received a single oral dose of midazolam 7.5 mg on day 1 followed by tenapanor 15 mg twice daily on days 2 to 15, with an additional single 7.5‐mg midazolam dose coadministered on day 15. Midazolam exposure was similar whether it was administered alone or with tenapanor (geometric least‐squares mean ratio [90%CI] for [midazolam + tenapanor]/midazolam: area under the concentration‐time curve, 107% [101% to 113%]; Cmax 104% [89.6% to 122%]). Findings were similar for metabolites of midazolam. These results indicate that tenapanor 15 mg twice daily does not have a clinically relevant impact on CYP3A4 in humans and suggest that tenapanor can be coadministered with CYP3A4‐metabolized drugs without affecting their exposure.